Is Enough Too Much? The dilemma for online distance learner supporters - Morgan, Christopher K.; McKenzie, Anthony D. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
We are a gregarious species, so it is not surprising that distance learners can be prone to feelings of isolation. In the days of traditional print-dominant distance education, attrition rates were often higher among distance learners than for their on-campus counterparts; but now, with the wider choice of communication options afforded by the online revolution, institutions have opportunity to look afresh at ways of compensating for the loneliness of long distance learners.However, teachers in higher education have their own problems. By viewing an online program as a human activity system, we identify an issue of growing concern concerning system maintenance; specifically, how system survival depends on meeting the human needs of those involved. The authors are not only concerned for distance learners, but also learning facilitators, many of whom face their own context-induced pressures. From the case of their own institutional setting, the authors demonstrate the need to manage the twin risks of student dropout and lecturer burnout.